Migration of Song Genres: Two Typical Lithuanian Cases - Ambrazevičius, Rytis (European Journal of Musicology, 2022)
Song genres are reconsidered and migrate similarly, in general terms of adaptation to new contexts, and differently depending on the certain actor milieus. In the present paper, these processes are illustrated applied to two examples of changing Lithuanian tradition.First, the song repertoire of Mištūnai village (southeastern Lithuania) is analysed and the vernacular emic attribution of the songs to genres is collated with their attribution to the scientifically defined “actual” genres. Thus, genres that change their assignment or lose their strict application and dissipate, in contrast with the relatively “stubborn” genres, are indicated. Musical and extramusical causes for such migrations/stability are discussed.Second, the song repertoires of the modern reconstructed Rasos (Midsummer) celebration, popular, first of all, amongst contemporary urban folk groups are discussed. These repertoires collect very different genres that were not used for this occasion in the past. They show significantly more courageous migrations, compared to the case of unbroken tradition in Mištūnai. Characteristic phenomena in the migrations that have resulted in the composing of a sort of “Rasos metagenre” are discussed.In order to offer an insight into the basics of Lithuanian songlore relevant for the subsequent discussion, the paper begins with a broad introduction of the general characteristics of Lithuanian traditional songs and their genres.